2009
DOI: 10.3354/meps08075
|View full text |Cite
|
Sign up to set email alerts
|

Diel variability of heterotrophic bacterial production and underwater UV doses in the eastern South Pacific

Abstract: Diel variability of heterotrophic bacterial production (BP) was investigated in the eastern South Pacific from October to December 2004. Three sites differing by their trophic status were studied: Marquesas Islands, the center (GYR) and the eastern South Pacific Gyre. By using a Lagrangian approach and high frequency measurements, an important increase (2-to 4-fold) in BP was observed at the 3 sites during the afternoon-sunset period within surface layers. To evaluate the impact of solar UV radiation on this v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The contribution of phytoplankton in the UV region was low (on average 6%–12%), despite the presence in this area of the southeast Pacific of mycosporine‐like amino acids (MAAs) [ Bricaud et al , 2010]. MAAs are UV‐absorbing compounds produced by phytoplankton cells to prevent harmful solar UV radiation, which has been shown to reach significant depths and affect biogeochemical compartments in the southeast Pacific waters [ Morel et al , 2007a; Tedetti et al , 2007; Sempéré et al , 2008; Van Wambeke et al , 2009]. Consequently, the distribution of nL w ( λ ) in the UV range was principally driven by CDM, without any or with only a very weak influence of phytoplankton (MAAs).…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of phytoplankton in the UV region was low (on average 6%–12%), despite the presence in this area of the southeast Pacific of mycosporine‐like amino acids (MAAs) [ Bricaud et al , 2010]. MAAs are UV‐absorbing compounds produced by phytoplankton cells to prevent harmful solar UV radiation, which has been shown to reach significant depths and affect biogeochemical compartments in the southeast Pacific waters [ Morel et al , 2007a; Tedetti et al , 2007; Sempéré et al , 2008; Van Wambeke et al , 2009]. Consequently, the distribution of nL w ( λ ) in the UV range was principally driven by CDM, without any or with only a very weak influence of phytoplankton (MAAs).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that heterotrophic bacteria might explain about a third of the c p spatial variability in oceanic regions (Montes-Hugo et al 2009). A diel cycle in the activity of free-living bacteria has been previously observed in the Mediterranean Sea (Gasol et al 1998;Mével et al 2008) as well as in other locations (Fuhrman et al 1985;Van Wambeke et al 2009), but their synchronicity with phytoplankton is not a general rule. Yet, a tight coupling between the photosynthetic extracellular release of organic material and its consumption by bacteria has been observed in the northwestern Mediterranean Sea (Gasol et al 1998;Mével et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Diurnal accumulation of DNA damage and nocturnal recovery have been also reported (Jeffrey et al 1996;Booth et al 2001). More recently, Van Wambeke et al (2009) observed that increases in the daily ultraviolet B : ultraviolet A ratios were negatively correlated with bacterial activity in South Pacific clear waters.…”
Section: Discussionmentioning
confidence: 99%